IMPLEMENTASI PENDIDIKAN KESEHATAN REPRODUKSI BAGI ANAK BERKEBUTUHAN KHUSUS DALAM PERSPEKTIF INKLUSIVITAS - Siska Syofiana; Insiatun Insiatun; Zulma Indra Rahmi Putri; Umri Rahman Efendi (Universitas Negeri Medan, 2026)
This study aims to examine the implementation of reproductive health education for Children with Special Needs (CSN) with consideration of inclusivity and effectiveness perspectives. The approach used is descriptive qualitative with a case study in several Special Needs Schools (SLB) and inclusive schools. Data were collected through in-depth interviews, participatory observations, and document analysis of relevant curriculum and teaching materials. The results indicate that while the importance of reproductive health education is recognized, many teachers still face challenges in teaching the subject due to a lack of training and support. The responses of CSN students to the material vary, with many needing visual explanations and adaptations in teaching methods. Parents also play a key role in supporting students' understanding, but there remains a sense of awkwardness when discussing this topic at home. The main obstacle faced is the lack of policies supporting the implementation of inclusive reproductive health education. Some schools have attempted innovations using visual media and technological applications to enhance students' understanding. In conclusion, to improve the inclusivity and effectiveness of reproductive health education for CSN, collaboration between teachers, parents, and supportive policies is needed to develop an adaptive and inclusive curriculum.